2021
DOI: 10.3389/fmicb.2021.736343
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Supernatant of Odoribacter splanchnicus Isolated From Human Feces Exhibits Anti-colorectal Cancer Activity

Abstract: The gut microbiota (GM) has been shown to be closely associated with the development of colorectal cancer (CRC). However, the involvement of GM is CRC has mainly been demonstrated by metagenomic profiling studies showing the compositional difference between the GM of healthy individuals and that of CRC patients and not by directly studying isolated gut microbes. Thus, to discover novel gut microbes involved in CRC, we isolated the GM from the feces of healthy individuals and evaluated its anti-CRC activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 66 publications
(72 reference statements)
0
14
1
Order By: Relevance
“…6 ). Interestingly, unlike our previous study that revealed only the CFS of O. splanchnicus , not live bacteria, exhibits anti-CRC activity in vivo ( 14 ), oral administration of E. callanderi live bacteria inhibited tumor growth in the mouse model. We speculated that orally administered E. callanderi can safely reach the gastrointestinal tract, leading to successful colonization, allowing it to exert anti-CRC effects by producing the same active molecules suggested in in vitro studies or different molecules in vivo , which has not been investigated in this study.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…6 ). Interestingly, unlike our previous study that revealed only the CFS of O. splanchnicus , not live bacteria, exhibits anti-CRC activity in vivo ( 14 ), oral administration of E. callanderi live bacteria inhibited tumor growth in the mouse model. We speculated that orally administered E. callanderi can safely reach the gastrointestinal tract, leading to successful colonization, allowing it to exert anti-CRC effects by producing the same active molecules suggested in in vitro studies or different molecules in vivo , which has not been investigated in this study.…”
Section: Discussioncontrasting
confidence: 88%
“…In a previous study, we screened the anti-CRC activity of gut microbes isolated from healthy Korean feces using their cell-free supernatants (CFSs) and discovered several CFSs with antiproliferative activity against colonic carcinoma cell lines ( 14 ). To identify one of the candidate microbes, we performed 16S rRNA gene sequencing and phylogenetic and phenotypic analyses, and discovered that it is E. callanderi (99.52% 16S rRNA gene similarity, rod-shaped without flagella).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…including B. caccae and B. vulgatus are known to be involved in destabilizing the colonic wall of the gut, potentially resulting in the progression of CRC 46 , 47 . At the same time, Odoribacter levels is shown to correlate with somatic mutations and cell proliferation resulting in poorer CRC prognosis 50 , 51 . Interestingly, differences in Bacteroidetes ASVs and Odoribacter splanchnicus were no longer observed after surgery when compared to NC individuals (Fig.…”
Section: Discussionmentioning
confidence: 99%